Mixed problem for the Petrovskii well-posed equation in a cylindrical domain - Iskenderov, B. A.; Guseinova, É. S. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We study the problem of existence and uniqueness of the solution of a mixed problem for the Petrovskii well-posed equation in a cylindrical domain and the behavior of this solution for large values of time.